Diseases of the urinarysystem of cows : 1. Clinical examination and urine analysis - S.. Al - Sammarrae, S. A.G; AI – Azawi, W. S.T. (The Iraqi Journal of Veterinary Medicine, 1999)
To study the diseases of the urinary system in cows, clinical examination including rectal palpation and urine samples from (697) cows were done in some farms, hospitals and two cattle stations (AI – Latifia and Al-Dijala) during the period July 1993 to April 1994. Clinical examination and rectal paplation of all cows in Al - Dijala station showed obvious clinical signs which indicat abnormalities in the urinary system . These include changes in the size of the kidneys with the presence or absence of lobulation . The ureter was palpable in some of these cows because of it’s enlargement and the bladder showed thickening of the wall. However all cows in the control group ( farms , hospitals & Ai - Latifia ) were free from any signs of urinary disturbances. The color of the urine in Al – Dijala was milky to cloudy red, and all samples were charcterized by small of ammonia. The specific gravity was low, and the urine pH was higher than normal , also all samles showed positive results for protein examination and only four cows showed positive results for benzidine test. The physical and chemical properties of the urine samples collected from control and Al - Latifia station cows were within the normal values. Examination of urine Sediment showed clear increase in the number of epithelial cells , pus cells and blood cells beside the presence of casts and bacteria in Al – Dijala station. The study concluded the close relationship between diseases of urinary and reprodective systems : Urinary system infection in Al - Dijala station cows were 100% because of a suspected out break of infectious pustule valvovaginitis which occur during the period of study, however the urine culture of Al - Latifia revealed the presence of 51 cows (19.69%) bacterial isolates.